Mentha longifolia Essential Oil from AlUla Region, Saudi Arabia: Chemical Composition and Classification - alnasri, Ebtihaj; Sindi, Heba (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
This study investigated the chemical composition and biological activities of Mentha longifolia (L.) essential oil from the AlUla region using GC-MS analysis, which identified 73 compounds with three predominant chemotypes: Piperitone epoxide (37.96%), 18-Cineole (16.37%), and menthone (10.01%). Total phenolic content analysis using the Folin-Ciocalteu method revealed 240.168 ± 2.1 mg gallic acid/mg/mL, while antioxidant activity showed a DPPH IC50 value of 30.66 µg/ml. antimicrobial assessment using agar well diffusion demonstrated stronger efficacy against Gram-positive compared to Gram-negative bacteria. Principal component analysis and Agglomerative Hierarchical Clustering identified four distinct chemotypes among the samples. Given its significant antimicrobial and antioxidant properties, these findings establish the potential of M. longifolia essential oil from the AlUla region as a natural preservative in food packaging applications. significant antibacterial and antioxidant activities. Therefore, it can be used as a natural preservative in food packaging.